Urinary Catheter Management for Nonurologists: A Resident Driven Educational Initiative. Issue 1 (January 2017) - Mossanen, Matthew; Winters, Brian; Lee, Franklin; Macleod, Liam C.; Haider, Maahum; Sutherland, Suzette E.; Olsen, Robin; Yang, Claire C.; Dalkin, Bruce; Choe, John; Gore, John L.
Abstract : Introduction: : Prevention of catheter associated urinary tract infection relies on timely catheter removal and care of indwelling catheters. Educational and quality improvement initiatives to prevent catheter associated urinary tract infection should address the basics of urinary catheter placement and management. Internal medicine residents are an appropriate target for these efforts and they may lack formal training in these issues. We developed a resident driven orientation session that covers basic Foley catheter management principles called the TIPS (Troubleshooting, Indications and Practice Sessions) program. Methods: : Urology residents at our institution were queried on common consultations for urinary catheter related issues. The incoming intern internal medicine class at our institution completed a pre‐TIPS survey that evaluated their baseline urological experience and knowledge. A 1‐hour didactic session led by urology residents was followed by hands‐on directed practice with mannequins. The web based survey was repeated 1 month later. Results: : Of the total of 60 residents 54 (90%) completed the initial survey. In medical school 38 of 54 residents (70%) had never rotated in urology. Upon repeating the survey at 1 month the response rate was 34 of 60 residents (57%). The proportion of residents confident in their ability to troubleshoot catheter problems increased from 50% to 88% (p <0.05). Knowledge of indications, clot retention and proper catheter technique also improved (p <0.05). Conclusions: : A focused educational session about common urological catheter management scenarios resulted in improved internal medicine resident confidence in catheter troubleshooting and knowledge of basic urinary catheter placement indications. These educational sessions may be a method to improve nonurology resident education and awareness of common urological issues.